Intramedullary Nailing vs Plating of the Fibula for Ankle Fractures in the Young Active Patient. Issue 1 (January 2022) - Bastias, Gonzalo F.; Mikenberg, Natalio R. Cuchacovich; Diaz, Felipe G.; Gutierrez, Paulina; Munoz, Gerardo; Melo, Rodrigo; Jofre, Magdalena I.; Filippi, Jorge
Category: Ankle; Trauma Introduction/Purpose: The use of fibular nailing (FN) for fixation of lateral malleolar fractures has been rising in recent years. Currently, it has been validated as an effective minimally invasive approach to ankle fractures specially in patients with high risk of wound dehiscence, diabetics and elderly low-demand patients. While most of the studies comparing the use of a fibula nail versus plating (PL) are carried out in this population at risk, the use of FN in younger patients with higher functional demands has been hardly studied. The aim of this study is to compare the functional and quality of life outcomes of patients treated with FN and PL in an active population. Methods: We performed an IRB-approved retrospective study including ankle fractures treated in our hospital from January 2017 to February 2020, with a minimum followup of one year. We included only patients between 18 and 55 years old treated by five fellowship-trained foot and ankle surgeons and divided into two groups according to the method of fixation of the fibula: intramedullary nailing (FN) or plating (PL). Demographics, medical comorbidities, type of fracture, reoperations and complications were collected. Functional and clinical evaluation included the Lower Extremity Functional Score (LEFS) and Short form 12 (SF 12) were obtained at an average of 28 months follow-up (range 14-50). Results: Eighty-five patients were included in this study with a mean age of 36.9 years old (range 16-55). The FN group was conformed by 31 patients (18 men) while the PL group consisted of 54 patients (32 men). Both groups were comparable in terms of age, sex, type of fracture, open fractures, number of malleoli compromised (P>0.05). Union was achieved in all patients. The complication rate was 3.2% (1 patient) in the FN group versus 5, 5% (3 patients) in the PL group (p=0.66). Two patients (6.5%) in the FN group and 7 patients (13%) in the PL group required hardware removal (p=0.36). There were no significant differences in SF-12 physical component (p=0.30), SF-12 Mental component (p=0.52) and LEFS Score (p=0.88). Conclusion: In this comparative study, there were no differences between the FN and PL groups for fixation of the fibula in terms of functional results and quality of life at an average of 28 months follow-up. Complications and hardware removal rates had no statistical differences between both groups. This is the first report on the literature comparing both fixation strategies on an active high-demand population.